Determination of cadmium in soil of Kota Samarahan - Ho, Chiw Peng (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Contamination of soil by heavy metals is a major environmental problem worldwide that need to be concerned. Among trace of elements that exist on the earth, cadmium (Cd) is said to be mostly originated from anthropogenic activities which can bring harmful effects to environment and human health. In this study, the samples were collected in 20 sampling sites at Kota Samarahan, Kuching, Malaysia. The samples were subjected to acid digestion and analysed by inductively coupled plasma optical emission spectrometry (ICP-OES). The Cd concentrations were ranged from 0.028-0.664 mg/kg where the mean Cd concentration for soils in UNIMAS and Muara Tuang area are 0.286 mg/kg and 0.188 mg/kg respectively. Both the mean Cd values from UNIMAS (P=0.018) and Muara Tuang (P=0.014) areas showed significant difference with the upper continental crust value. However, independent t-test analysis showed that the mean Cd concentration in UNIMAS area is not significantly different from that of Muara Tuang area (P=0.180). Soil contamination assessment was derived via geoaccumulation index (Igeo) and certain location was found to be moderately to strongly contaminated with the maximum Igeo values of 2.12. Besides, results obtained from Pearson’s correlation indicated that there is no significant difference between soil parameters (pH, SOM and clay content) and Cd concentration. The soil in Kota Samarahan is categorised as moderately contaminated to strongly contaminated soil with overall mean Cd concentration of 0.237±0.160 mg/kg based on analysis and assessment conducted on UNIMAS and Muara Tuang area.